Differential Response of Mouse Thymic Epithelial Cell Types to Ionizing Radiation-Induced DNA Damage - Calvo-Asensio, Irene; Barthlott, Thomas; von Muenchow, Lilly; Lowndes, Noel F.; Ceredig, Rhodri (Frontiers in Immunology, 2017)
Thymic epithelial cells are the main components of the thymic stroma, which supports and controls T-cell development. Preparative regimens using DNA damaging agents such as total body irradiation (TBI) and/or chemotherapeutic drugs that are necessary prior to bone marrow transplantation (BMT) have profound deleterious effects on the hematopoietic system, including the thymic stroma, which may be one of the main causes for the prolonged periods of T-cell deficiency and the inefficient T cell reconstitution that are common following BMT. The DNA Damage Response is a complex signaling network that allows cells to respond to all sorts of genotoxic insults. Hypoxia is known to modulate the DDR and play a role affecting the survival capacity of different cell types. In this study, we have characterized in detail the DDR of cortical and medullary thymic epithelial cell lines and their response to ionizing radiation, as well as the effects of hypoxia on their DDR. Although both mTECs and cTECs display relatively high radio-resistance, mTEC cells have an increased survival capacity to IR-induced DNA damage, and hypoxia specifically decreases the radio-resistance of mTECs by up-regulating the expression of the pro-apoptotic factor Bim. Analysis of the expression of TEC functional factors by primary mouse TECs showed a marked decrease of highly important genes for TEC function and confirmed cTECs as the most affected cell type by IR. These findings have important implications for improving the outcomes of BMT and promoting successful T cell reconstitution.